Poles’ “Specific Peculiarity”. Cultural Myths as a Tool for Common Identity Description - Krakowiak, Małgorzata (Sensus Historiae, 2020)
The article contains the deliberation concerning the Polish nation self-stereotype. Different texts, modern and ancient, representing high and popular culture (e.g. Słowacki’s poems, Gombrowicz’s memories, interviews and feuilletons from temporary press as well art exposition catalogues). The author puts the questions about the characteristic features of Polish people and their collective identity. The problems described were shown as an integral component of the temporary cultural myths.